Pengaruh Modal dan Bahan Baku Terhadap Pendapatan Melalui Produksi Pengrajin Patung Kayu di Kecamatan Sukawati Kabupaten Gianyar - Suartawan, Komang; Purbadharmaja, Ida Bagus (E-Jurnal Ekonomi Pembangunan Universitas Udayana; vol.6.No. 9. September 2017(pp.1628-1867), 2017)
Craft industry has a very important role in Bali in general and in Gianyar regency especially in providing employment opportunities for the community. The purpose of this study was to analyze 1) the direct effect of capital and raw materials to production, 2) the direct effect of capital, raw materials and production revenue, 3) Effect of capital and raw materials to revenue indirectly through production craftsmen wooden sculptures in the District Sukawati Gianyar.Penelitian District was conducted in Gianyar regency with a wooden statue of respondents craftsmen, which includes District Sukawati. The samples in this research were 72 respondents. Data collection methods used in this study using interviews. The data analysis technique used is the analysis track / path analysis. Based on the results obtained the conclusion that the capital and raw materials direct and significant effect on the production of wood sculpture craftsmen. Variable capital, raw materials and the production of a direct and significant effect on the income of wooden sculptures handicraft industry in the district Sukawati Gianyar Regency. Production variables are variables mediating indirect effect variable capital and raw materials on income. Keywords : Capital, Raw Materials, Income, Production